Composite single-core power cable

By using self-healing composite cores, nanographene reinforced conductors, temperature-sensitive insulation layer and waterproof and corrosion-resistant outer sheath in composite single-core power cables, the problem that microcracks and insulation layer performance cannot be adjusted during long-term operation is solved, efficient self-repair, enhanced conductivity and improved insulation performance, and improved cable service life and operation safety are improved.

CN120089453AInactive Publication Date: 2025-06-03DONGTAI WANSHUNTONG WIRE & CABLE CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202510265276.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-06-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing composite single-core power cables are prone to microcracks during long-term operation, lack effective repair methods, and the performance of the insulation layer cannot be adjusted according to temperature changes, resulting in limited operating temperature range.

Method used

A composite core consisting of carbon fiber, glass fiber and a resin matrix containing self-healing microcapsules is used. The conductor layer is composed of nanographene-reinforced aluminum conductors, the insulating layer is made of temperature-sensitive polymer material, and the outer sheath is waterproof and corrosion-resistant material.

Benefits of technology

The composite core is self-repaired after microcracks appear, which improves the conductivity and fatigue resistance of the conductor layer. The insulation layer adjusts heat dissipation and insulation effects according to temperature changes. The outer sheath improves corrosion resistance and waterproof performance, extends the service life and operation safety of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120089453A_ABST
    Figure CN120089453A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of power transmission, and discloses a composite single-core power cable, comprising: a composite core composed of carbon fibers, glass fibers and a resin matrix containing a self-repairing microcapsule, the self-repairing microcapsule being capable of releasing a repairing monomer and repairing a microcrack when the composite core generates the microcrack; the conductor layer is arranged around the composite core and is composed of an aluminum conductor containing nano graphene; the insulating layer wraps the conductor layer and is made of a temperature-sensitive polymer material; and the outer sheath wraps the insulating layer and is made of a waterproof corrosion-resistant material. The composite core of the cable can recover more than 90% of original strength (the loss of tensile strength after repair is only 3%, which is recovered from 580Ksi to 570Ksi) within 24 hours after microcracks (such as the depth of 10mu m) generated by mechanical stress or fatigue in the operation process, and the self-repairing mechanism does not need manual intervention or external equipment, so that the self-repairing performance is greatly improved. And the sudden failure of the traditional cable caused by micro-damage accumulation is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power transmission, and particularly to a composite single-core power cable. Background Art

[0002] In the prior art, composite single-core power cables have been widely used in the field of high-voltage power transmission. Their typical structure is designed with a composite core in combination with an aluminum conductor to improve performance. The composite core is usually made of a resin matrix reinforced with carbon fiber and glass fiber, and is formed by pultrusion process. It has a relatively high tensile strength (generally between 450 - 650 MPa) and a relatively low coefficient of thermal expansion (about 1.5×10 -6 / °C). A single-layer aluminum conductor is wrapped around the periphery to form a single-core structure. Such cables perform excellently in overhead power transmission lines. Compared with traditional aluminum conductor steel-reinforced (ACSR) cables, their weight is reduced by about 60%, and they can operate at relatively high temperatures (such as above 90°C), improving the current-carrying capacity and transmission efficiency. There are already related products on the market that significantly improve the capacity of power transmission lines by optimizing the cross-sectional area of the aluminum conductor and the strength of the composite core. Some technologies can even double the capacity without replacing the tower, and are widely used in long-distance power transmission.

[0003] However, the existing composite single-core power cables have obvious deficiencies in practical applications. Firstly, their design is mainly aimed at the overhead environment and does not fully meet the requirements of underground power transmission. For example, they lack sufficient waterproof and corrosion resistance capabilities in humid or corrosive soils, resulting in easy aging of the sheath and shortened service life when used underground. Secondly, the composite core is prone to generating microcracks under the influence of mechanical stress or fatigue during long-term operation. Currently, there is a lack of effective repair means for such damage, and the accumulation of damage may lead to core fracture, especially increasing potential safety hazards in scenarios where underground maintenance is inconvenient. In addition, the performance of the insulation layer of the existing cables is relatively fixed and cannot adjust the heat dissipation or insulation effect according to temperature changes. It is prone to overheating at high temperatures and the insulation efficiency is not optimal at low temperatures, restricting the operating temperature range and overall safety. At the same time, the composite core and the conductor mostly adopt a layered structure, with insufficient interfacial bonding strength, prone to peeling, affecting the current-carrying capacity and long-term durability, and it is difficult to meet the higher requirements of modern high-voltage power transmission for high efficiency and high reliability. Summary of the Invention

[0004] Aiming at the deficiencies of the prior art, the present invention provides a composite single-core power cable, which solves the problem that the existing composite core is prone to generating microcracks under the influence of mechanical stress or fatigue during long-term operation.

[0005] To achieve the above object, the present invention is realized through the following technical solutions: A composite single-core power cable, comprising:

[0006] Composite core, composed of carbon fiber, glass fiber and a resin matrix containing self-healing microcapsules, wherein the self-healing microcapsules can release repair monomers and repair the microcracks when microcracks occur in the composite core;

[0007] Conductor layer, arranged around the composite core, composed of an aluminum conductor containing nano-graphene, and the conductor layer is combined with the composite core through an integrated molding process;

[0008] Insulating layer, covering the conductor layer, composed of a temperature-sensitive polymer material, and the insulating layer can adjust the heat dissipation performance or insulating performance according to temperature changes;

[0009] Outer sheath, covering the insulating layer, composed of a waterproof and corrosion-resistant material.

[0010] Preferably, the self-healing microcapsules account for 5-10% of the volume of the resin matrix, the diameter of the microcapsules is 10-50 μm, the repair monomer is a two-component epoxy resin, and the strength loss of the composite core after repair is less than 5%.

[0011] Preferably, the carbon fiber and glass fiber of the composite core are mixed in a mass ratio of 1:1, the carbon fiber is arranged in a helical winding manner, the winding angle is 30-45°, and the diameter of the composite core is 5-8 mm.

[0012] Preferably, the content of nano-graphene in the conductor layer is 0.5-1% of the aluminum conductor, the conductivity of the conductor layer is greater than 65 IACS, and the integrated molding process is a high-temperature co-extrusion process.

[0013] Preferably, the temperature-sensitive polymer material includes a polyurethane matrix and a doped temperature-sensitive phase change material, the melting point of the phase change material is 60-80 °C, when the temperature is higher than 70 °C, the heat dissipation coefficient of the insulating layer increases by more than 20%, and when the temperature is lower than 30 °C, the insulation resistance of the insulating layer is greater than 1014 Ω·m.

[0014] Preferably, the outer sheath is made of polyethylene material, with a thickness of 3-5 mm, and the thickness of the insulating layer is 1-2 mm.

[0015] Preferably, the upper limit of the operating temperature of the cable is 120 °C, and the current-carrying capacity is more than 50% higher than that of a traditional composite single-core power cable with the same diameter.

[0016] Preferably, a manufacturing method of a composite single-core power cable includes the following steps:

[0017] S1. Mix carbon fiber and glass fiber and immerse them in an epoxy resin containing self-healing microcapsules, and prepare a composite core through a pultrusion process;

[0018] S2. Add nano-graphene to the aluminum melt, and coat the aluminum melt outside the composite core through a high-temperature co-extrusion process to form a conductor layer;

[0019] S3. Extrude a temperature-sensitive polymer material outside the conductor layer to form an insulating layer;

[0020] S4. Coat a waterproof and corrosion-resistant material outside the insulating layer to form an outer sheath.

[0021] Preferably, in step S1, the forming temperature of the pultrusion process is 180 - 220 °C; in step S2, the extrusion temperature of the high-temperature co-extrusion process is 650 - 700 °C.

[0022] Preferably, in step S3, the temperature-sensitive polymer material is coated by an extruder, and the extrusion temperature is 200 - 250 °C; in step S4, the outer sheath is formed by secondary extrusion.

[0023] The present invention provides a composite single-core power cable. It has the following beneficial effects:

[0024] 1. The composite core of the cable of the present invention can restore more than 90% of the original strength within 24 hours for micro-cracks (such as 10 μm in depth) generated due to mechanical stress or fatigue during operation (the tensile strength loss after repair is only 3%, restored from 580 Ksi to 570 Ksi). This self-repair mechanism does not require manual intervention or external equipment, avoiding sudden failure caused by the accumulation of micro-damage in traditional cables.

[0025] 2. The insulating layer of the cable of the present invention uses a temperature-sensitive polymer (such as polyurethane doped with paraffin particles), which absorbs heat through the melting of the phase change material when the temperature exceeds 70 °C, and the heat dissipation coefficient is increased by 25% (up to 0.35 W / m·K), effectively preventing insulation failure caused by overheating; at low temperature (<30 °C), the insulation resistance is as high as 10^15 Ω·m, and the breakdown voltage is increased by 20% to 40 kV / mm. This dynamic thermal management function enables the upper limit of the cable operating temperature to reach 120 °C, significantly improving the operating safety and transmission efficiency.

[0026] 3. The cable of the present invention realizes a 55% increase in current capacity (from 800 A to 1250 A) through an ultra-thin composite core (6 mm in diameter, reducing materials by 20%) and a nano-graphene enhanced conductor (conductivity 66 IACS), the transmission efficiency per unit weight is increased by 30%, the overall weight is only 1.2 kg / m (18% lighter than traditional ones), and the integrated co-extrusion process enables the shear strength at the interface between the conductor and the core to reach 50 MPa, avoiding the risk of peeling, and the fatigue resistance is increased by 40%.

[0027] 4. The outer sheath of the present invention is made of high-density polyethylene doped with 2.5% nano-zinc oxide (particle size 30 nm). After being immersed in 5% NaCl solution for 30 days, the corrosion depth is only 0.02 mm, and the corrosion resistance is improved by 35%. The sheath with a thickness of 4.5 mm also has excellent waterproof performance (water permeability < 0.1%). This characteristic protects the internal composite core and conductor layer from the erosion of the underground humid environment, ensuring the stable operation of the cable in high-humidity or saline-alkali soil.

[0028] 5. The cable of the present invention is manufactured by a step-by-step process (S1-S4). When pultruding the composite core, the curing temperature is precisely controlled at 180-220 °C, and the finished product rate reaches 98%. High-temperature co-extrusion (680 °C) ensures seamless bonding between the conductor and the core, shortening the production cycle by 15% (it takes about 2 minutes for each meter of cable). Surface treatment (such as silane coupling agent) and equipment parameter optimization (screw speed 50 rpm) in the process improve the product consistency by 20%. The hardness of the core body is stable at Shore D82. This efficient production method reduces the manufacturing cost by 10%. Description of the Drawings

[0029] Figure 1 is the internal structure sectional view of a composite single-core power cable of the present invention;

[0030] Figure 2 is the flow chart of the manufacturing method of a composite single-core power cable of the present invention.

[0031] Among them, 1. Composite core; 2. Conductor layer; 3. Insulation layer; 4. Outer sheath. Detailed Embodiments

[0032] Next, the technical solutions of the present invention will be clearly and completely described in conjunction with the drawings of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0033] Please refer to the attached Figure 1 , the embodiment of the present invention provides a composite single-core power cable, including:

[0034] A composite core 1, which is composed of carbon fiber, glass fiber, and a resin matrix containing self-healing microcapsules. Among them, the self-healing microcapsules can release repair monomers and repair microcracks when microcracks occur in the composite core 1;

[0035] A conductor layer 2, which is arranged around the composite core 1 and is composed of an aluminum conductor containing nano-graphene. The conductor layer 2 and the composite core 1 are combined by an integrated molding process;

[0036] The insulating layer 3, covering the conductor layer 2, is made of a temperature-sensitive polymer material, and the insulating layer 3 can adjust the heat dissipation performance or insulation performance according to temperature changes;

[0037] The outer sheath 4, covering the insulating layer 3, is made of a waterproof and corrosion-resistant material.

[0038] Specifically, for the carbon fiber of the composite core 1, Toray T700 model (tensile strength 4900 MPa) is selected, and for the glass fiber, E-glass (tensile strength 3400 MPa) is selected. The two are mixed by a wet winding process. The carbon fiber is wound around the glass fiber bundle at a spiral angle of 35° to form a core body with a diameter of 6 mm. The resin matrix uses bisphenol A epoxy resin (viscosity 500 mPa·s), and 8% by volume of self-healing microcapsules are added. The microcapsules are composed of a urea-formaldehyde resin shell (wall thickness 2 μm) wrapping a two-component repair monomer (monomer A is an epoxy monomer, and monomer B is an amine curing agent), and are uniformly distributed in the resin through an ultrasonic dispersion process. The conductor layer 2 selects aluminum with a purity of 99.7%, doped with 0.8% by mass of single-layer graphene (flake diameter 5 - 10 μm), and is co-extruded with the composite core 1 through a twin-screw extruder at 680 °C, with an extrusion rate of 2 m / min, to form a conductor layer 2 with a thickness of 3 mm. The insulating layer 3 uses polyurethane (Shore A85 hardness), doped with 7% by mass of paraffin particles (melting point 70 °C, particle size 20 μm), and is coated through a single-screw extruder at an extrusion temperature of 230 °C, with a thickness of 1.5 mm. The outer sheath 4 selects high-density polyethylene (density 0.95 g / cm 3 ), and 2% of nano-zinc oxide is added to improve the corrosion resistance. It is formed through a secondary extrusion process, with a thickness of 4 mm and a cooling rate of 5 °C / s.

[0039] Beneficial effects: The self-healing function enables the cable to recover 90% of its strength within 24 hours after microcracks appear; the integrated molding reduces the risk of interface peeling, and the overall tensile strength is increased to 650 Ksi; the temperature-sensitive insulating layer 3 has a 25% increase in heat dissipation efficiency at 80 °C, and the low-temperature insulation resistance reaches 1015 Ω·m, ensuring the safety of underground high-voltage power transmission; the corrosion resistance of the outer sheath 4 is increased by 30%, making it suitable for humid environments.

[0040] The self-healing microcapsules account for 5 - 10% of the volume of the resin matrix, the diameter of the microcapsules is 10 - 50 μm, the repair monomer is a two-component epoxy resin, and the strength loss of the composite core 1 after repair is less than 5%.

[0041] Specifically, the self-healing microcapsules are prepared by the microemulsion method. The shell material, urea-formaldehyde resin, is formed by in-situ polymerization. They contain a two-component epoxy resin (monomer A with a viscosity of 300 mPa·s and monomer B with a viscosity of 200 mPa·s). The diameter of the microcapsules is controlled at 30 μm, the wall thickness is 2.5 μm, and they account for 8% of the resin volume. They are mixed with the epoxy resin by high-speed stirring (1500 rpm). When the composite core 1 is formed, the pultrusion speed is 0.5 m / min, the curing temperature is 200 °C, and the uniformity of the distribution of the microcapsules in the resin reaches over 95%. In the repair experiment, a 10-μm deep microcrack is applied to the surface of the composite core 1. After the microcapsules rupture, the monomers are released and polymerize to form a repair layer within 24 hours. The thickness of the repair layer is about 15 μm, and the hardness is the same as that of the original resin (Shore D80). The strength test is carried out using a universal tensile machine, and the tensile strengths before and after repair are 580 Ksi and 570 Ksi respectively.

[0042] Beneficial effects: The 8% proportion of microcapsules balances the repair ability and the core stiffness. The repair efficiency is high, and the strength loss is only 3%, significantly reducing the failure risk caused by microcracks; the repair process does not require external intervention, reducing the underground cable maintenance cost by more than 50%.

[0043] The carbon fiber and glass fiber in the composite core 1 are mixed at a mass ratio of 1:1. The carbon fiber is arranged in a helical winding manner, and the winding angle is 30 - 45°. The diameter of the composite core 1 is 5 - 8 mm.

[0044] Specifically, when the carbon fiber and glass fiber are mixed, continuous fiber bundles are used. The single-filament diameter of the carbon fiber is 7 μm, and the single-filament diameter of the glass fiber is 10 μm. They are synchronously wound through an impregnating tank (containing epoxy resin) at a mass ratio of 1:1. The carbon fiber covers the outside of the glass fiber bundle at a 35° helical angle, and the winding tension is controlled at 20 N. The thickness of the winding layer is 0.5 mm. During pultrusion molding, the die diameter is 6 mm, the traction speed is 0.6 m / min, the curing furnace is divided into three sections (180 °C, 200 °C, 220 °C), and the total curing time is 15 min. The surface roughness Ra of the core is controlled below 0.8 μm to ensure tight bonding with the conductor layer 2. The tensile strength test result is 620 Ksi, and the coefficient of thermal expansion is 1.5×10 -6 / °C.

[0045] Beneficial effects: The helical winding increases the transverse shear strength by 30%. The ultra-thin design with a diameter of 6 mm reduces the material usage by 20% and reduces the cable weight by 15%; the low coefficient of thermal expansion reduces the high-temperature sag, is suitable for narrow underground channels, and improves the installation efficiency.

[0046] The content of nano-graphene in the conductor layer 2 is 0.5 - 1% of the aluminum conductor. The conductivity of the conductor layer 2 is greater than 65 IACS, and the integrated molding process is a high-temperature co-extrusion process.

[0047] Specifically, the conductor layer 2 is made of aluminum ingots (purity 99.7%), heated to 720°C in a melting furnace, and 0.8% graphene nanosheets (thickness 1 nm, sheet diameter 8 μm) are added. They are dispersed evenly through ultrasonic stirring (frequency 20 kHz, power 500 W), with a stirring time of 30 min, and the graphene distribution uniformity reaches 98%. The co-extrusion process uses a twin-screw extruder, with an extrusion temperature of 680°C, a screw speed of 50 rpm, a thickness of the conductor layer 2 of 3.2 mm, a cooling water tank temperature of 20°C, and a cooling time of 10 s. The conductivity is tested using the four-probe method, and the result is 66 IACS, with a resistivity of 1.65×10 -8 Ω·m. The interfacial shear strength is measured through a tensile test and is increased to 45 MPa.

[0048] Beneficial effects: Graphene doping increases the conductivity by 10%, increases the current capacity by 55%, and reduces the energy loss by 15%; high-temperature co-extrusion ensures seamless bonding between the conductor and the core, improves the fatigue resistance by 40%, and extends the service life.

[0049] The thermosensitive polymer material includes a polyurethane matrix and a doped thermosensitive phase change material. The melting point of the phase change material is 60 - 80°C. When the temperature is higher than 70°C, the heat dissipation coefficient of the insulating layer 3 increases by more than 20%. When the temperature is lower than 30°C, the insulation resistance of the insulating layer 3 is greater than 1014 Ω·m.

[0050] Specifically, the thermosensitive polymer is polyurethane (molecular weight 50,000), and 8% paraffin microparticles (melting point 72°C, particle diameter 25 μm) are added through melt blending. The mixing temperature is 180°C, the stirring speed is 300 rpm, and the mixing time is 20 min. When coating with an extruder, the screw diameter is 50 mm, the speed is 40 rpm, the temperature is divided into three zones (200°C, 230°C, 220°C), the thickness of the insulating layer 3 is 1.8 mm, and the surface finish Ra is 0.5 μm. The heat dissipation test is carried out at 80°C. After the phase change material melts, the heat dissipation coefficient reaches 0.35 W / m·K. The insulation resistance test result at low temperature (25°C) is 1015 Ω·m, and the breakdown voltage is 40 kV / mm.

[0051] Beneficial effects: The thermosensitive design improves the heat dissipation efficiency by 28% at high temperatures, preventing overheating failure; it has excellent insulation performance at low temperatures, the breakdown voltage is increased by 20%, enhancing the operation safety of underground cables and adapting to temperature differences.

[0052] The outer sheath 4 is made of polyethylene material, with a thickness of 3 - 5 mm, and the thickness of the insulating layer 3 is 1 - 2 mm.

[0053] Specifically, the outer sheath 4 is made of high-density polyethylene (melt index 0.8 g / 10 min), with 2.5% nano-zinc oxide (particle size 30 nm) added. It is mixed through a twin-screw extruder at a temperature of 190 °C, a rotation speed of 60 rpm, and a mixing time of 15 min. During the secondary extrusion, the die temperature is 200 °C, the extrusion thickness is 4.5 mm, and it is cooled in a cold water bath (15 °C) with a cooling rate of 6 °C / s. The surface hardness of the sheath is Shore D65. The thickness of the insulation layer 3 is controlled at 1.6 mm, the extrusion temperature is 235 °C, and the shrinkage rate after cooling is less than 0.5%. The corrosion resistance test (5% NaCl solution, 30 days) shows that the corrosion depth is only 0.02 mm.

[0054] Beneficial effects: The waterproof and corrosion resistance of the outer sheath 4 are improved by 35%, protecting the internal structure from underground moisture erosion; the insulation layer 3 is thin and uniform, reducing the material cost by 10% and enhancing the overall flexibility of the cable.

[0055] The upper limit of the operating temperature of the cable is 120 °C, and the current-carrying capacity is more than 50% higher than that of a traditional composite single-core power cable with the same diameter.

[0056] Specifically, the total diameter of the cable is controlled at 20 mm. The operating temperature test is to continuously operate at 120 °C for 1000 hours. The sag of the composite core 1 is only 0.3%, and the resistance increase of the conductor layer 2 is less than 2%. The current-carrying capacity test uses a DC power supply. Compared with a traditional ACCC cable (diameter 20 mm, capacity 800 A), the capacity of this cable reaches 1250 A. The weight test result is 1.2 kg / m, which is 18% lighter than the traditional cable. The durability test (5000 cycles of load) shows that the performance decay is less than 5%.

[0057] Beneficial effects: It operates stably at high temperatures, with a capacity increase of 56%, suitable for high-load underground power transmission; the lightweight design reduces the installation difficulty by 20% and reduces the tower base or pipeline support cost.

[0058] Please refer to the attached Figure 2 , a manufacturing method of a composite single-core power cable, comprising the following steps:

[0059] S1. Mix carbon fiber and glass fiber and immerse them in epoxy resin containing self-healing microcapsules, and prepare the composite core 1 through a pultrusion process;

[0060] S2. Add nano-graphene to the aluminum melt, and coat the aluminum melt outside the composite core 1 through a high-temperature co-extrusion process to form the conductor layer 2;

[0061] S3. Extrude a temperature-sensitive polymer material outside the conductor layer 2 to form the insulation layer 3;

[0062] S4. Coat a waterproof and corrosion-resistant material outside the insulation layer 3 to form the outer sheath 4.

[0063] Specifically, in S1: Carbon fiber (T700) and glass fiber (E-glass) are mixed through an impregnation tank (resin concentration 60%), microcapsules are dispersed by ultrasonic waves (25 kHz), with a content of 8%, the diameter of the pultrusion die is 6 mm, the curing temperature is 200 °C, and the traction speed is 0.5 m / min. In S2: 0.8% graphene is added to the aluminum melt (720 °C), stirred for 40 min, the co-extrusion temperature is 680 °C, the screw speed is 55 rpm, and the conductor thickness is 3 mm. In S3: Polyurethane and paraffin are mixed (180 °C), the extrusion temperature is 230 °C, the thickness is 1.5 mm, and the cooling time is 8 s. In S4: 2% zinc oxide is added to polyethylene, the extrusion temperature is 200 °C, the sheath thickness is 4 mm, and it is cooled with cold water (15 °C).

[0064] Beneficial effects: The process is simple and efficient, the production cycle is shortened by 15%, and the product yield reaches 98%; the combination of self-repair and high conductivity improves the reliability of the cable by 50%.

[0065] In step S1, the forming temperature of the pultrusion process is 180 - 220 °C; in step S2, the extrusion temperature of the high-temperature co-extrusion process is 650 - 700 °C.

[0066] Specifically, in S1, the pultrusion equipment is equipped with three heating zones (180 °C, 200 °C, 220 °C), the die length is 1 m, the traction tension is 25 N, the surface of the core is coated with a silane coupling agent (0.5%), and the hardness after curing is Shore D82. In S2, the co-extruder is equipped with a twin screw (diameter 60 mm), the preheating zone is 650 °C, the forming zone is 680 °C, the cooling zone is 30 °C, and the bonding strength between the conductor layer 2 and the core reaches 50 MPa.

[0067] Beneficial effects: Precise temperature control improves the uniformity of the core by 20%, and the co-extrusion strength is increased by 35%, ensuring product consistency and durability.

[0068] In step S3, the thermosensitive polymer material is coated by an extruder, and the extrusion temperature is 200 - 250 °C; in step S4, the outer sheath 4 is formed by secondary extrusion.

[0069] Specifically, in S3, the extruder is equipped with a screw with an L / D ratio of 25:1, the three-zone temperature is (200 °C, 235 °C, 220 °C), the extrusion pressure is 10 MPa, the thickness deviation of the insulation layer 3 is ±0.1 mm, and the cooling water temperature is 18 °C. In S4, the secondary extrusion uses a double-layer die, the inner layer temperature is 195 °C, the outer layer is 200 °C, the sheath thickness deviation is ±0.2 mm, the surface roughness is Ra 0.6 μm, and there is no breakdown in the withstand voltage test (10 kV, 30 min).

[0070] Beneficial effects: The extrusion accuracy is improved by 15%, the insulation and the sheath provide coordinated protection, and the withstand voltage performance is improved by 25%.

[0071] Although embodiments of the present invention have been shown and described, those of ordinary skill in the art will appreciate that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite single-core power cable, characterized in that: include: A composite core (1) is composed of carbon fibers, glass fibers and a resin matrix containing self-repairing microcapsules, wherein the self-repairing microcapsules are capable of releasing repair monomers and repairing the microcracks when microcracks are generated in the composite core (1); A conductor layer (2) is arranged around the composite core (1) and is composed of an aluminum conductor containing nanographene, wherein the conductor layer (2) and the composite core (1) are combined through an integrated molding process; an insulating layer (3), covering the conductor layer (2), and made of a temperature-sensitive polymer material, wherein the insulating layer (3) can adjust heat dissipation performance or insulation performance according to temperature changes; The outer sheath (4) covers the insulating layer (3) and is made of a waterproof and corrosion-resistant material.

2. The composite single-core power cable according to claim 1, characterized in that: The self-repairing microcapsules account for 5-10% of the volume of the resin matrix, the diameter of the microcapsules is 10-50 μm, the repairing monomer is a two-component epoxy resin, and the strength loss of the composite core (1) after repair is less than 5%.

3. The composite single-core power cable according to claim 1, characterized in that: The carbon fibers and glass fibers of the composite core (1) are mixed in a mass ratio of 1:1, the carbon fibers are arranged in a spiral winding manner, the winding angle is 30-45°, and the diameter of the composite core (1) is 5-8 mm.

4. The composite single-core power cable according to claim 1, characterized in that: The content of nanographene in the conductor layer (2) is 0.5-1% of the aluminum conductor, the conductivity of the conductor layer (2) is greater than 65 IACS, and the integrated molding process is a high-temperature co-extrusion process.

5. The composite single-core power cable according to claim 1, characterized in that: The temperature-sensitive polymer material comprises a polyurethane matrix and a doped temperature-sensitive phase-change material, the melting point of the phase-change material is 60-80° C., when the temperature is higher than 70° C., the heat dissipation coefficient of the insulating layer (3) is increased by more than 20%, and when the temperature is lower than 30° C., the insulation resistance of the insulating layer (3) is greater than 1014Ω·m.

6. The composite single-core power cable according to claim 1, characterized in that: The outer sheath (4) is made of polyethylene material and has a thickness of 3-5 mm, and the insulation layer (3) has a thickness of 1-2 mm.

7. The composite single-core power cable according to claim 1, characterized in that: The upper limit of the operating temperature of the cable is 120° C., and the current capacity is increased by more than 50% compared with the traditional composite single-core power cable with the same diameter.

8. A method for manufacturing a composite single-core power cable, characterized in that: The composite single-core power cable according to any one of claims 1 to 7 comprises the following steps: S1, mixing carbon fiber and glass fiber and immersing the mixture in epoxy resin containing self-repairing microcapsules to prepare a composite core (1) by pultrusion process; S2, adding nanographene to aluminum melt, and coating the aluminum melt on the outside of the composite core (1) through a high-temperature co-extrusion process to form a conductor layer (2); S3, extruding a temperature-sensitive polymer material outside the conductor layer (2) to form an insulating layer (3); S4. Covering the insulating layer (3) with a waterproof and corrosion-resistant material to form an outer sheath (4).

9. The method for manufacturing a composite single-core power cable according to claim 8, characterized in that: In the step S1, the molding temperature of the pultrusion process is 180-220°C; in the step S2, the extrusion temperature of the high-temperature co-extrusion process is 650-700°C.

10. The method for manufacturing a composite single-core power cable according to claim 8, characterized in that: In the step S3, the temperature-sensitive polymer material is coated by an extruder at an extrusion temperature of 200-250° C.; in the step S4, the outer sheath (4) is formed by secondary extrusion.

Citation Information

Cited By

  • Low-voltage fireproof cable and preparation method thereof

    CN120496966A

  • Crosslinked polyethylene insulated corrosion-resistant power cable

    CN120913935A

  • Superconducting semi-rigid cable made of high-purity aluminum and preparation method thereof

    CN121054328A

  • Lightweight superconductive carbon fiber composite cable and preparation method thereof

    CN121964267A

  • A lightweight self-healing cable and its preparation method

    CN122575805A